Variations of Exon 2-3 of the Branched Chain Keto Acid Dehydrogenase E1 Subunit Alpha (BCKDHA) Gene and Its Flanking Intronic Region in Madura Cattle - Febriana, Asri; Farajallah, Achmad; Wahidah, Baiq Farhatul; Perwitasari, Dyah (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2022)
Indonesia is one of a country with high biodiversity and genetic resources. One of them is Madura cattle that derived from crossing between exotic cattle, namely zebu cattle with local Indonesian cattle, namely Bali cattle. Branched-chain alpha-keto acid dehydrogenase is an enzyme complex that metabolizes branched chain amino acids, namely valine, leucine and isoleucine. This study aimed to analyze exons 2-3 variation of the BCKDHA gene and its flanking region in Madura cattle. The sequences of it were obtained using DNA sequencing techniques. A total of seven variations were found, one variation located in the flanking region adjacent to the 5' end of exon 2 of the BCKDHA gene. The A392G variation found in exon 3 does not cause any amino acid changes. There is no variation found in exon 2, it indicates that the exon regions of BCKDHA gene are more conserved than introns in the Madura cattle.